Combinatorial testing: using blocking to assign test cases for validating complex software systems. Issue 2 (3rd April 2021) - Lekivetz, Ryan; Morgan, Joseph
Abstract : Testing complex software systems is an extraordinarily difficult task. Test engineers are faced with the challenging prospect of ensuring that a software system satisfies its requirements while working within a strict budget. Choosing a test suite for such an endeavour can be framed as a design of experiments problem. Combinatorial testing is a software testing methodology that may be viewed as a design of experiments approach to addressing the software testing challenge. We extend this methodology by introducing the concept of blocking factors for a test suite. We provide an example, using an open source software library, to illustrate our extension. Advantages of considering blocks are discussed, both in the design as well as after test execution, when fault localisation may be necessary.